Effects of different light intensities and damage caused by mirids on cocoa photosynthesis - Muhamad, R.; Hee, Y. S.; Abullah, A. M.; Awang, M. B. (2001)
Studies were undertaken to determine the relationship between Helopeltis theivora Waterhouse cocoa shoot damage and photosynthetic activity (Pn) under different light intensities in natural environment. Young cocoa shoots (shoots with green-reddish soft leaves) were used in all the field experiments. Shoots were exposed to different light intensities of 10, 25, 50 and 75% of total/full sunlight. In Ihe first experiment, five adults of the cocoa mirids were introduced to the cages for 24 hours and subsequently the number of lesions produced by the insects under different light intensities were recorded. In the second experiment, cocoa shoots which had been exposed 10 different levels of damage caused by H. thelvora (low, medium and heavy damage) were subjected to different light, as of in the first experiment (10 to 75% light intensities). Three replicates of uniform size cocoa shoots were selected and photosynthetic activity was determined immediately after the predisposition to the mirids. The photosynthetic activity (Pn) of the shoots was determined using a portable photosynthesis system. Results obtained showed that there were significant differences in the number lesions caused by Helopeltis when they were caged with different light intensities. The highest damage was observed on shoots that received 25% light intensity (mean of 15.0 +- 0.8 lesions). Cocoa shoots that received 10% and 75% light intensity had the least attack of 6 and 8 lesions respectively, and 11 lesions on those exposed to 50% light intensity. The rate of photosynthesis of cocoa shoots exposed to four light regimes also showed significant differences between the treatments. Highest rate of photosynthetic activity was observed on cocoa shoots exposed to 75% light regime (5.1 umol m-2 s-1) followed by 50% and 25% light with 4.5 and 2.7 umol m-2 s-1 respectively. Shoots exposed to 10% light had the lowest photosynthetic activity with only 0.6 umol m-1 s-1. Damage by the mirids (low, medium and high damage) also caused reduction in the photosynthetic rate of the cocoa shoots. Significant reduction was observed especially when the shoots were badly damaged. Results obtained showed that the lowest damage caused by the mirid was observed on shoots exposed to 75% light intensities. This light regime coincides with the highest photosynthetic activity of the shoots. The shoots may be able to compensate damage caused by the mirids although at heavy damage the photosynthetic acivity was drastically reduced.